Optical defocus affects differently ON and OFF visual pathways - Carmen Pons; Reece Mazade; Jianzhong Jin; Mitchell W. Dul; Jose-Manuel Alonso (iScience)
Summary: The human eye has a crystalline lens that focuses retinal images at different viewing distances. Optical defocus reduces the spatial resolution and contrast of these retinal images and spectacle lenses minify or magnify their size. Because light and dark stimuli are processed with ON and OFF pathways that have different spatial resolution, contrast sensitivity and size suppression, optical defocus, and image magnification should affect differently the two pathways. Our results provide support for this prediction. We show that optical defocus expands ON receptive fields while shrinking OFF receptive fields and decreases OFF more than ON pathway responses whereas magnification shrinks OFF more than ON receptive fields. These ON-OFF pathway modulations could be used during eye growth to optimize the size and brightness of retinal images by maximizing the retinal response, a mechanism that could be shared across species and may have implications in visual diseases such as myopia (nearsightedness).